ENHANCING STUDENTS’ WRITING SKILL BY USING BRAINSTORMING STRATEGY - ZIZI NURHIKMAH (Merwinspy Publisher, 2023)
This research has aim for increasing students’ writing skill. For increasing students’ skill, it is needed an effective strategy. This research used brainstorming for it. In the method, the researcher used Classroom Action Research. It had done for 2 cycles with total six meeting. Two meetings was for test and four meetings were for treatment.The population of this research was the tenth grade students from eleventh grade students of Marketing at Vocational High School of Sunan Kalijogo Malang. Academic year 2022/2023. The students’ average was 60 then after the implementation brainstorming their cycle changed into 77,43. It showed that brainstorming strategy can improve students’ writing skill.